HPTLC Fingerprinting and Validation of Quercetin Yield of Gel Formulation for Diabetic Neuropathic Pain - Raikwar, Ankita; Kumar Posa, Mahesh; Panda, Subhranshu; Shamsuzzman, Md. (Journal of Neonatal Surgery, 2025)
Background: The growing global dependence on herbal medicines highlights the urgent need for validated analytical techniques to ensure their quality, safety, and therapeutic efficacy. This study aimed to develop and validate a High-Performance Thin Layer Chromatography (HPTLC) method for the quantitative estimation of quercetin, a potent antioxidant flavonoid, in a polyherbal formulation. Material and Methods: HPTLC method was developed using a mobile phase composed of toluene: ethyl acetate (9:1 v/v), which provided a sharp, well-resolved peak for quercetin at an Rf value of 0.892. Method validation was performed according to ICH Q2 (R1) guidelines, evaluating specificity, linearity, accuracy, precision, robustness, and sensitivity parameters. Results: The method showed excellent linearity over the concentration range of 1000–5000 ng/spot, with a correlation coefficient (r²) of 0.999. The limit of detection (LOD) and limit of quantification (LOQ) were determined as 60.67 ng/spot and 174.00 ng/spot, respectively. Accuracy was confirmed through recovery studies, yielding results between 99.12% and 99.85%. Intra-day precision exhibited %RSD values below 2%, demonstrating high repeatability. Robustness tests indicated the method’s resilience to slight variations in experimental conditions. The quercetin content in the gel formulation was found to be approximately 13.76 mg/g. Conclusion: The developed HPTLC method is simple, accurate, and reliable for the quantitative estimation of quercetin in polyherbal formulations. It is suitable for routine quality control and standardization, supporting the safety and efficacy of herbal medicinal products. ..